Effect of phosphate and temperature on force exerted by white muscle fibres from dogfish - Park-Holohan, S.-J. (Springer Netherlands, 2010)
Effects of Pi (inorganic phosphate) are relevant to the in vivo function of muscle because Pi is one of the products of ATP hydrolysis by actomyosin and by the sarcoplasmic reticulum Ca(2+) pump. We have measured the Pi sensitivity of force produced by permeabilized muscle fibres from dogfish (Scyliorhinus canicula) and rabbit. The activation conditions for dogfish fibres were crucial: fibres activated from the relaxed state at 5, 12, and 20°C were sensitive to Pi, whereas fibres activated from rigor at 12°C were insensitive to Pi in the range 5–25 mmol l(−1). Rabbit fibres activated from rigor were sensitive to Pi. Pi sensitivity of force produced by dogfish fibres activated from the relaxed state was greater below normal body temperature (12°C for dogfish) in agreement with what is known for other species. The force-temperature relationship for dogfish fibres (intact and permeabilized fibres activated from relaxed) showed that at 12°C, normal body temperature, the force was near to its maximum value.